Comparative Study on Relationship Between Inconsistent Online-Offline Social Performance and Self-Efficacy of University Students Based on Types of Social Activity - Yang, Yang; Dongdong, Yan; Yu, Hu (Frontiers in Psychology, 2021)
Social behavior is closely linked to self-efficacy, which has been shown to impart a significant impact on the academic performance and mental well-being of university students. The advent of social media has cultivated inconsistency in online and offline social behavior of university students, an issue that has come to prominence in scholarly research. However, the relationship between this inconsistency and self-efficacy is a worthwhile subject to investigate because little research has been conducted into this particular confluence of behavioral concepts. This paper integrates online and offline social behavior, establishes a typology for university student social activities and investigates the correlation between different types of social activity and student self-efficacy, with a specific focus on those with notable inconsistencies in their social performance. The following are the findings of our study: First, as online social networking has become the dominant form of social interaction, the types of social activity have increased, with one-third of university students showing inconsistent online and offline social behavior. However, different types of social activities have varied effects on the self-efficacy of university students, with differences between general self-efficacy, which is significantly above academic self-efficacy and social self-efficacy. These effects are also different for students with inconsistent online and offline social performance; those who are active online show higher self-efficacy than those who are active offline. This study shows online social network interactions to be more closely related to student self-efficacy than offline interactions.